2011
DOI: 10.1111/j.1365-2494.2011.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Past lessons and future prospects: plant breeding for yield and persistence in cool‐temperate pastures

Abstract: Pastoral-based animal production systems are under increasing pressure to provide the high quantity and quality of feed needed for optimal ruminant performance. The capacity of farmers to increase forage yield further, solely by increasing fertilizer inputs or through improved pasture management, is limited. Emerging requirements to balance industry production targets against the need to reduce greenhouse gas emissions and N losses pose further challenges. Plant breeding is being asked to deliver results more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
138
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(155 citation statements)
references
References 63 publications
1
138
2
2
Order By: Relevance
“…While overall DM yield gain is significant across varieties registered on RLs over the past 40 years, gains in DM production in pasture deficit periods such as spring and autumn may well be viewed of higher economic value by farmers for commercial use especially as pasture performance comes under increased pressure due to limitations in land availability and environmental constraints in the future (Parsons et al 2011), Sampoux et al (2011 identified over 40 years, gains in DM yield of perennial ryegrass varieties released on European National lists were primarily in the summer and autumn but no gain was achieved in spring DM yield production where pasture supplementation requirements are at their highest. Gain in DM yield may very well need to be assessed on such pasture growth deficit periods in the year to ensure farmers are reaping maximum economic benefit from newly bred recommended varieties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While overall DM yield gain is significant across varieties registered on RLs over the past 40 years, gains in DM production in pasture deficit periods such as spring and autumn may well be viewed of higher economic value by farmers for commercial use especially as pasture performance comes under increased pressure due to limitations in land availability and environmental constraints in the future (Parsons et al 2011), Sampoux et al (2011 identified over 40 years, gains in DM yield of perennial ryegrass varieties released on European National lists were primarily in the summer and autumn but no gain was achieved in spring DM yield production where pasture supplementation requirements are at their highest. Gain in DM yield may very well need to be assessed on such pasture growth deficit periods in the year to ensure farmers are reaping maximum economic benefit from newly bred recommended varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations to land availability coupled with increasing environmental requirements to reduce greenhouse gas emissions and N losses to ground water are placing increased pressure on grass based animal production systems to provide additional quantities of high quality forage. The ability of farmers to increase forage yield, through increased fertiliser inputs is limited (Parsons et al 2011). Thus, increased performance must be achieved by other means and one of the most important avenues is grass breeding.…”
Section: Introductionmentioning
confidence: 99%
“…The constraints the pasture base places on the reliability of supply of a high nutritive value diet supportive of milk production has been long recognised (Jacobs and McKenzie 2003). Much research effort over the past decade has been directed at addressing this challenge through the integration of other forage species into a predominantly perennial ryegrass feedbase (Farina et al 2011, Tharmaraj et al 2014, or trying to improve the seasonality or total production of perennial ryegrass (Parsons et al 2011. A recent review of these activities identified that this strategy was most successful when the additional species/strategy was perennial focussed, directly grazeable and responsive to N fertilizer and irrigation inputs.…”
Section: Introductionmentioning
confidence: 99%
“…The energy supplied by a feed is a function of its digestibility, which has traditionally been a major target for plant breeding programmes (Kingston-Smith and Thomas, 2003;Parsons et al, 2011a). Increasing the digestibility of feed DM is a good way of increasing its energy use efficiency, although other factors are increasingly important forage breeding targets (Casler and van Santen, 2010).…”
Section: Trends In Breeding For Qualitymentioning
confidence: 99%
“…Rumen ammonia concentrations are more constant during the day with increased WSC concentrations in the grass (Lee et al, 2002). In fresh grass-based diets, there is a curvilinear relationship between the dietary ratio of WSC to nitrogen and the proportional excretion of dietary nitrogen in urine (Parsons et al, 2011a). This relationship suggests that a high diet WSC : N ratio will increase the efficiency of nitrogen use by dairy cows, even if milk production is not affected.…”
Section: Trends In Breeding For Qualitymentioning
confidence: 99%